PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wati, Rouli Erna; Yando, Agus Defri (SCIENTIA JOURNAL, 2021)
In this research, there’s a purpose to know influence of good corporate governance and leverage on financial performance in manufacturing companies are listing on IDX. The population is amounted 61 companies consumer goods industry sectors. Sampling technique using method purposive sampling obtained by samples of 16 companies. The types data in research is a secondary information form of financial report obtained through the IDX. The data analysis method is multiple regression which is processed using the SPSS version 21. The result of the t test indicate that institutional ownership, managerial ownership, audit committee and debt to equity ratio have no significant effect on financial performance and the proportion of independent board of commissioners partially has a significant negative effect on financial performance. The result F test showed simultaneously the variables of institutional ownership, managerial ownership, proportion of independent board of commissioners, audit committee, and debt to equity ratio have a significant effect on financial performance.Keywords: Good Corporate Governance; Leverage;Financial Performance.